Kondisi Empiris Penyederhanaan Eselon III dan IV pada Pemerintah Kota Sorong - Andri Irawan; Burhanudin Mukhamad Faturahman (Inovasi, 2021)
Efficient and responsive improvement of public services can be done through echelons simplification and multiplying functional positions that are directly oriented to the service. However, the policy has not been implemented by the Sorong City Government because it has specificity and resistance from local officials. The purpose of this writing describes and analyzes the empirical condition of simplification of echelon III and IV of Sorong City Government. The research method uses a descriptive qualitative approach. The results showed that the echelonsimplification III and IV of Sorong City Government has not been implemented because it did not get support from the Mayor. Bureaucratic culture in the echelon promotion system prioritizes personal and hereditary closeness is the main obstacle to echelons simplification of Sorong city government. In addition, the pride of the social status of echelon positions and the absence of new functional position building agencies makes the ASN mindset focused on echelon positions only and local governments have difficulty placing ASN in the appropriate agencies of the new functional position. Supervision instruments for new functional positions have also not yet properly constructed. The legality aspect, there is no legal regulation from the ASN law derivatives on the new functional position system. The process of switching structural to functional positions based on personal and hereditary proximity makes the function of the ASN merit system not optimal so that until now the echelons simplification of the Sorong City Government has not been carried out. The merit system can work if the behavior of bureaucrats prioritizes service over culture. This study recommends that the central government arrange a mapping of new functional position transitions in Sorong City Government and local assessorinstitutions. In addition, it is necessary to change the mindset of echelon officials by making legislation restricting the facilities of echelon officials.Keywords:empirical condition, simplification of echelon III and IV, Sorong City Governmen